Buchach – a city at the meeting point of different national narratives - Woldan, Alois (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Our article presents three different historic narratives of the city of Buchach in former Eastern Galicia, a Polish, Jewish and Ukrainian one, according to the city’s mixed population, consisting of a larger Jewish, a smaller Polish and a still smaller Ukrainian group. The Polish historic narrative is represented by Sadok Barącz’s book “Pamiątki buczackie”, the Ukrainian one by the Historical and Memoiristical Collection “The City of Buchach and its Region”, compiled by emigration writers, and the Jewish narrative by Y.S. Agnon’s “A City in its Fulness”. These sources provide different ways of presenting history, sometimes converging and sometimes diverging from each other, which is illustrated by the depiction of selected historic events: the siege of the city by Chmelnicki’s troops in 1648, the role of the city in the Polish-Turkish war of 1672, the importance of Austrian rule since 1772 for the city, and the city’s fate in the time of World War I and immediately after the war. Our comparison of the above three historic narratives ends with the re-evaluation of the figure of Mikołaj Potocki, Polish nobleman, who today is held in high esteem by Ukrainian historians of art because of his function as a founder of the most beautiful buildings in Buchach and a sponsor of famous artists, creators of these architectural monuments. He is seen as a mediator between the Polish and Ukrainian tradition.

Artykuł prezentuje trzy różne narracje narodowe na temat historii miasta Buczacz w byłej Galicji wschodniej, polską, żydowską i ukraińską, odpowiednio do trzech grup etnicznych, z których składało się społeczeństwo miasta. Reprezentatywne dla narracji polskiej są „Pamiątki buczackie” Sadoka Barącza, dla ukraińskiej szkice historyczne i wspomnienia w tomie „Bučač i Bučaččyna”, które zostały zebrane przez autorów emigracji, dla żydowskiej fikcyjna historia miasta „A City in its Fulness” Y. S. Agnona. W tych interpretacjach znajdują się różne sposoby postrzegania, które częściowo się pokrywają, częściowo również są ze sobą sprzeczne. Pozwala to ukazać opis określonych wydarzeń historycznych: oblężenie miasta przez wojska Bohdana Chmielnickiego 1648, jego rolę w polsko-tureckiej wojnie z 1672, znaczenie czasu austriackiego dla miasta i losów miasta w czasie I wojny światowej oraz bezpośrednio potem. To porównanie zostaje zakończone oceną postaci historycznej, magnata Mikołaja Potockiego, który jako budowniczy miasta Buczacz i jako mecenas wielkich artystów jest postrzegany dzisiaj, szczególnie przez stronę ukraińską, jako swoisty łącznik narodowych tradycji.
Keywords: Buchach; Barącz, S.; Agnon, Y.S.; Potocki, M.; Buczacz; Sadok Barącz; Mikołaj Potocki